Calculus Bovis Sativus Improves Bile Acid Homeostasis via Farnesoid X Receptor-Mediated Signaling in Rats With Estrogen-Induced Cholestasis - Xiang, Dong; Yang, Jinyu; Liu, Yanan; He, Wenxi; Zhang, Si; Li, Xiping; Zhang, Chenliang; Liu, Dong (Frontiers in Pharmacology, 2019)
Cholestatic diseases are characterized by toxic bile acid (BA) accumulation, and abnormal BA composition, which subsequently lead to liver injury. Biochemical synthetic Calculus Bovis Sativus (CBS) is derived from natural Calculus Bovis, a traditional Chinese medicine, which has been used to treat hepatic diseases for thousands of years. Although it has been shown that CBS administration to 17α-ethinylestradiol (EE)-induced cholestatic rats improves bile flow and liver injury, the involved underlying mechanism is largely unknown. In this study, we showed that CBS administration to EE-induced cholestatic rats significantly decreased serum and hepatic BA levels and reversed hepatic BA composition. DNA microarray analysis suggested that the critical pathways enriched by CBS treatment were bile secretion and primary BA synthesis. These findings led us to focus on the effects of CBS on regulating BA homeostasis, including BA transport, synthesis and metabolism. CBS enhanced hepatic BA secretion by inducing efflux transporter expression and inhibiting uptake transporter expression. Moreover, CBS reduced BA synthesis by repressing the expression of BA synthetic enzymes, CYP7A1 and CYP8B1, and increased BA metabolism by inducing the expression of metabolic enzymes, CYP3A2, CYP2B10, and SULT2A1. Mechanistic studies indicated that CBS increased protein expression and nuclear translocation of hepatic and intestinal farnesoid X receptor (FXR) to regulate the expression of these transporters and enzymes. We further demonstrated that beneficial effects of CBS administration on EE-induced cholestatic rats were significantly blocked by guggulsterone, a FXR antagonist. Therefore, CBS improved BA homeostasis through FXR-mediated signaling in estrogen-induced cholestatic rats. Together, these findings suggested that CBS might be a novel and potentially effective drug for the treatment of cholestasis.